Subclinical Hypothyroidism and Female Infertility (Iraqi Journal of Medical Sciences, 2016)
Background : Thyroid disorders are amongst the commonest endocrine disorders in women of childbearing age. Population-based infertility data of women with subclinical hypothyroidism are not available.Objective: Assess the role of subclinical hypothyroidism in female infertility.Methods: A prospective clinical study of 40 infertile women with subclinical hypothyroidism treated with thyroxine after exclusion of the basic causes of infertility in Wasit Governorate-Iraq from June 2006 until June 2009 (3 years). Result: 24 of the women (60%) were complaining of primary infertility with infertility period ranged from 1-6 years and 16 (40%) with secondary infertility with infertility period range from 1-5 years. Pretreatment mean TSH level was 7.6 mIU/L which normalized after treatment to a mean level 1.9 mIU/L. Conception was recorded in 14 (35%) women during the period of the study however, only 11 pregnants succeeded to continue pregnancy resulting in a live birth rate of 27.5%.Conclusions: Our results support the role of subclinical hypothyroidism as a predisposing factor for female infertility that should not be forgotten.Key words: subclinical hypothyroidism, female infertility, thyroxine supplementation
Keywords: subclinical hypothyroidism; female infertility; thyroxine supplementation